A genetic model provides evidence that the receptor for atrial natriuretic peptide (guanylyl cyclase-A) inhibits cardiac ventricular myocyte hypertrophy - Kishimoto, Ichiro (The National Academy of Sciences, 2001)
Guanylyl cyclase-A (NPR-A; GC-A) is the major and possibly the only receptor for atrial natriuretic peptide (ANP) or B-type natriuretic peptide. Although mice deficient in GC-A display an elevated blood pressure, the resultant cardiac hypertrophy is much greater than in other mouse models of hypertension. Here we overproduce GC-A in the cardiac myocytes of wild-type or GC-A null animals. Introduction of the GC-A transgene did not alter blood pressure or heart rate as a function of genotype. Cardiac myocyte size was larger (approximately 20%) in GC-A null than in wild-type animals. However, introduction of the GC-A transgene reduced cardiac myocyte size in both wild-type and null mice. Coincident with the reduction in myocyte size, both ANP mRNA and ANP content were significantly reduced by overexpression of GC-A, and this reduction was independent of genotype. This genetic model, therefore, separates a regulation of cardiac myocyte size by blood pressure from local regulation by a GC-mediated pathway.